Decentralizing money: Bitcoin prices and blockchain security - PAGNOTTA, Emiliano Sebastian (Institutional Knowledge at Singapore Management University, 2022)
We address the determination of bitcoin prices and decentralized security. Users forecast the transactional and resale values of holdings, pricing the risk of systemic attacks. Miners contribute resources to protect against attackers and compete for block rewards. Bitcoin's design leads to multiple equilibria: the same blockchain technology is consistent with sharply different price and security levels. Bitcoin's monetary policy can lead to welfare losses and deviations from quantity theory. Price-security feedback amplifies fundamental shocks' volatility impact and leads to boom and busts unconnected to fundamentals. We characterize how viability versus fiat currency depends on bitcoin's relative acceptability and inflation protection.